Triglyceride-Rich Lipoproteins Are Responsible for Thrombin Generation Induced by Lipid Peroxides - Barrowcliffe, T W; Gray, E; Kerry, P J; Gutteridge, J M C (Thrombosis and Haemostasis, 1984)
Previous studies have shown that lipid peroxides promote thrombin generation in platelet-poor plasma. In the present study, it has been shown that triglyceride-rich lipoproteins, especially chylomicra of dietary origin, are responsible for this procoagulant activity. The generation of thrombin by lipid peroxides is also enhanced by their inhibitory action on antithrombin III. These results suggest a possible new relationship between dietary fat, lipid peroxidation and thrombus formation.
Keywords: Lipid peroxides; Lipoproteins; Coagulation